2008
DOI: 10.17221/59/2008-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Selected properties of European beech (Fagus sylvatica L.)

Abstract: ABSTRACT:The paper deals with the variability of tree-ring width, with the density and swelling (volumetric swelling and swelling in individual anatomical directions) of wood from two different locations. Further, the variability of the explored properties along the stem radius is researched. The ring analyses show that the ring width decreases along the stem radius from the pith to the stem outer perimeter. Location 2 (a lower altitudinal vegetation zone) had on average wider rings (a statistically insignific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 5 publications
1
16
1
Order By: Relevance
“…tance moisture meter, FMD6 Brookhuis, and kiln drying). Density (ρ 0 ) was measured after a 24-h drying period at 103°C ± 2°C (Vavrčík and Gryc 2012), resulting in 696 kg m -3 (beech) and 439 kg m -3 (spruce wood) which is in agreement with observations from other authors (Gryc et al 2011, Gryc et al 2008). …”
Section: Methodssupporting
confidence: 85%
“…tance moisture meter, FMD6 Brookhuis, and kiln drying). Density (ρ 0 ) was measured after a 24-h drying period at 103°C ± 2°C (Vavrčík and Gryc 2012), resulting in 696 kg m -3 (beech) and 439 kg m -3 (spruce wood) which is in agreement with observations from other authors (Gryc et al 2011, Gryc et al 2008). …”
Section: Methodssupporting
confidence: 85%
“…The study of Kord et al (2010) reported a pattern of increasing wood density from the pith to the bark for Populus euramericana. On the other hand, Gryc et al (2008b) found a downward trend in that direction for European beech. In the case of willow, no impact of the horizontal position in a stem on the wood density value was confirmed (SennerbyForsse 1989).…”
Section: Resultsmentioning
confidence: 90%
“…31 Vine [61] Vitis vinifera Phenols, flavonols, flavonoids, ascorbic acid, anthocyanin, catalase, peroxidase, polyphenol oxidase 32 Walnut [62] Juglans nigra quinones, oils, tannins; nuts contain essential fatty acids, including cis-linoleic and alfa-linolenic, Nucin or Juglon 33 White Chestnut [63] Aesculus hippocastanum Quercetin and kaempferol, polyphenols 34 Wild Oat [64,65] Bromus ramosus Avenanthramides, saponins, phytoalexin and flavonoids such as vitexin and isovitexin 35 Wild Rose [66,67] Rosa canina Vitamin C, total polyphenols, and total flavonoids 36 Willow [68,69] Salix …”
Section: Role Of Flower Essences In Health Carementioning
confidence: 99%